Numerical modeling and experimental study of solution-blown nonwovens formed on a rotating drum. (22nd November 2016) - Ghosal, Arkaprovo; Sinha-Ray, Sumit; Sinha-Ray, Suman; Yarin, Alexander L.; Pourdeyhimi, Behnam
Abstract: In this work the three-dimensional architecture and properties of solution-blown laydown formed on a rotating drum are studied using the system of quasi-one-dimensional equations of the dynamics of free liquid polymer viscoelastic jets moving, evaporating and solidifying, while being driven by a surrounding high-speed air jet. Solution blowing of multiple polymer jets simultaneously issued from a nosepiece and collected on a rotating drum is modelled numerically. The numerical results on the volumetric porosity of nonwoven laydown are compared with the experimental data of the present work. The numerical predictions are in good agreement with the experimental data and elucidate the effect of the angular drum velocity on the mass and angular fiber distribution, as well as the volumetric porosity and permeability of the solution-blown nonwovens. It was found that instead of doing any upstream modification of the solution blowing process, the easiest way to control the laydown structure (the mass and angular fiber distribution, as well as the volumetric porosity and permeability) is to vary the angular velocity of the collecting drum. Graphical abstract: Highlights: Numerical simulation of solution blowing process. Prediction of three-dimensional architecture of laydown. Prediction of mass distribution, porosity and permeability of laydown. Experiments with solution blowing with nanofiber collection on a rotating drum. Comparison of the theory and experiments.